2020
DOI: 10.3390/biom10101457
|View full text |Cite
|
Sign up to set email alerts
|

Updating Phospholipase A2 Biology

Abstract: The phospholipase A2 (PLA2) superfamily contains more than 50 enzymes in mammals that are subdivided into several distinct families on a structural and biochemical basis. In principle, PLA2 has the capacity to hydrolyze the sn-2 position of glycerophospholipids to release fatty acids and lysophospholipids, yet several enzymes in this superfamily catalyze other reactions rather than or in addition to the PLA2 reaction. PLA2 enzymes play crucial roles in not only the production of lipid mediators, but also membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
142
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(147 citation statements)
references
References 221 publications
3
142
0
2
Order By: Relevance
“…Macrophage functions are regulated by several PLA 2 s, including Pla2g5, Pla2g4a, Pla2g10, and Pla2g2d which may contribute to PL remodeling during activation [ 26 , 43 , 45 ]. Notably, Pla2g5 mRNA is induced in macrophages by IL-4 but not LPS+IFNγ [ 20 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophage functions are regulated by several PLA 2 s, including Pla2g5, Pla2g4a, Pla2g10, and Pla2g2d which may contribute to PL remodeling during activation [ 26 , 43 , 45 ]. Notably, Pla2g5 mRNA is induced in macrophages by IL-4 but not LPS+IFNγ [ 20 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an imbalance between pro and anti-inflammatory lipids could account for the different role of Pla2g5 in the pathogenesis of several pathologies. Additionally, the expression of Pla2g5 in hematopoietic vs. non-hematopoietic cells could also determine the function of Pla2g5 in different diseases [ 25 , 26 ]. A recent study showed that in endothelial cells, the expression of Pla2g5 mRNA is higher than other PLA 2 s (Pla2g1b, 2a, 2d, 2e, 2f, and 10) then its expression is reduced by Angiotensin II stimulation while Pla2g5 protein is still present on the cell surface, likely linked to proteoglycans [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…for their catalytic activity, principally targeting phospholipids in the extracellular milieu. sPLA2s are widely distributed in different body fluids (e.g., snake and other venoms, plasma, pancreatic juice, tears, seminal fluid) and are involved in a variety of processes, from snakebite envenomation to signal transduction, to lipid mediator production and dietary lipids digestion in mammals [6,8,9]. Moreover, it is important to consider that snake venom PLA2s toxins are potential therapeutic drugs against many pathophysiological conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Based on their dependence on Ca 2+ and cellular localization, these enzymes are generally classified into several families [ 4 , 5 , 6 ]. Three of these families are the most studied in terms of cellular signaling and lipid mediator production: the Ca 2+ -dependent cytosolic phospholipase A 2 s, the Ca 2+ -dependent secreted phospholipase A 2 s, and the Ca 2+ -independent phospholipase A 2 s. In this respect, the contribution by Murakami et al [ 7 ] provides a timely overview of the functioning of members of these three major phospholipase A 2 families in several pathophysiological conditions, ranging from host defense and metabolism to cancer and skin barrier function.…”
mentioning
confidence: 99%